Peningkatan Mutu dan Efisiensi Pelayanan Kesehatan melalui Implementasi Rekam Medis Elektronik di RSUD Budhi Asih - Nurul Dwi Ariani; Nuke Dewi Utami Hamid; Nadia Rizki Pratami; Jajat Sudrajat; Sani Fitriyani; Candra Mecca Sufyana (PADMA, 2025)
The development of information technology in the healthcare sector encourages hospitals to adapt to digital systems, particularly through the implementation of Electronic Medical Records (EMR). This system plays an essential role in improving the quality and efficiency of healthcare services by enabling faster, more accurate, and integrated processes. This community service activity aims to enhance the knowledge and skills of healthcare workers and administrative staff in using the EMR system as part of hospital digital transformation. The program was carried out through three stages: preparation, implementation, and evaluation. During the implementation stage, participants took part in socialization and hands-on training to understand the concept, benefits, and operational use of the EMR system. An educational and participatory approach was applied, allowing participants to be actively involved in simulations of digital patient data management. The results showed an improvement in participants’ understanding and operational skills related to the EMR system. Participants realized that the use of electronic systems can accelerate healthcare services, improve documentation accuracy, and maintain patient data confidentiality. Furthermore, this activity fostered awareness of the importance of digital transformation within hospitals to support services that are more efficient, high-quality, and patient-centered.